Regional and Annual Variability in Subglacial Sediment Transport by Water for Two Glaciers in the Swiss Alps - Delaney, Ian; Bauder, Andreas; Werder, Mauro A.; Farinotti, Daniel (Frontiers in Earth Science, 2018)
Glaciers expel large amounts of water and sediments, and the discharge of both is influenced by glacier retreat. Because the majority of sediment originates subglacially, as opposed to proglacially, focus must be given to subglacial sediment discharge. The latter, however, is poorly constrained. We present a subglacial sediment transport time-series from the Gornergletscher and Aletschgletscher catchments in the Swiss Alps, based on hourly suspended sediment transport data and bedload transport estimates. This dataset is used to identify interannual and regional variability and to quantify the relationship between sediment transport and water discharge. Analysis of the relationship suggests that the access of water to subglacial sediment exerts substantial control on the quantity of sediment discharged. Historical data from Gornergletscher since the 1970's show that elevated amounts of sediment were discharged in the 1980's, following the onset of increasing glacier melt. However, by 2016 and 2017, the sediment discharge had returned to quantities below those in the 1970's, suggesting that sediment discharge may return to an equilibrium over decadal times scales following the onset of a new hydrological regime. Erosion rates for the two catchments (0.28 mm a−1 to 0.49 mm a−1) are lower than in other glacierized catchments of the Swiss Alps ( 1 mm a−1). In some years in both catchments, these rates are even less than a third of those reported in earlier decades, highlighting substantial regional and interannual variability in catchment-scale erosion. Empirical models of the relationship between sediment concentration and water discharge, calibrated with the presented 2016–2017 data, fail to capture the elevated sediment discharge over the 1980's. This suggests that processes other than runoff, such as changing access to subglacial sediment by meltwater, were responsible for the increase. Subglacial sediment discharge depends on both water discharge and sediment availability. Therefore, we argue that physically-based models of subglacial sediment transport, that can capture its complex temporal and spatial evolution in response to glacier retreat, are needed to predict and understand a glacier's sediment yield.